IDENTIFIKASI KESULITAN BELAJAR SISWA DAN UPAYA PENANGGULANGANNYA PADA SISWA KELAS III DI SDN GUGUS 04 KECAMATAN PUJUT KABUPATEN LOMBOK TENGAH TAHUN AJARAN 2020/2021 - Nunung Apriana; Darmiany Darmiany; Siti Istiningsih (Renjana Pendidikan Dasar, 2021)
The purpose of this study was to determine student learning difficulties and efforts to overcome them in grade III students at SDN Gugus 04, Pujut District, Central Lombok Regency. The research method used is a qualitative method of phenomenological type with a descriptive approach. Sources of data in this study were teachers and third grade students of SDN Gugus 04, Pujut District, Central Lombok Regency, amounting to 3 teachers and 15 students. Determination of research result sources in this study using purposive sampling technique. The research result collection method used was interviews, observation, and documentation. The researchresult obtained were analyzed using interactive data analysis techniques analysis model of Miles and Huberman. Based on the results of interviews and observations, it can be concluded that there are 5 students who still have difficulty reading and there are 5 students who still have difficulty writing.